Analisa Kemampuan Karyawan Hotel Griya Sintesa Muara Enim dalam Memahami Sistem Informasi Hotel yang Menggunakan Bahasa Inggris - Indah Wati; M Taslim; Destra Amni; Luthfia Renalda Tania; Muhammad Luthifar Syach Anwar (Jurnal Pendidikan dan Sastra Inggris, 2025)
In the hospitality industry, hotel information systems are predominantly operated in English, posing linguistic challenges for staff with limited English proficiency. This study aims to analyze the English comprehension ability of employees at Hotel Griya Sintesa Muara Enim, particularly in understanding English-based hotel information systems. Using a quantitative descriptive approach, data were collected through a written vocabulary test (comprising 20 multiple-choice and matching items), semi-structured interviews, and documentation from 30 front-office and operational staff members. Descriptive statistical analysis revealed an average correct-response rate of 69.2% (mean score = 70.5), placing overall comprehension in the “Paham” (Understand) category. While most employees could operate the system functionally, difficulties persisted with technical terms such as PMS, interface, database error, and backup file. Key contributing factors include limited prior English training, infrequent exposure to technical vocabulary, and reliance on peer assistance. The findings suggest that staff's functional English proficiency is sufficient for daily operations but requires targeted support to enhance accuracy and confidence. Recommendations include implementing English for Hospitality Systems training, developing an in-house English terminology glossary, and establishing an internal mentoring program. This study underscores the importance of integrating language support into hospitality technology adoption to ensure operational efficiency and service quality.